HISTOLOGICAL CONSEQUENCES OF CONSUMPTION OF ENERGY DRINK ON RENAL TUBULES: Energy Drink and Renal Tubules - Rasheed, Ammara; Aslam, Imtiaz; Tafweez, Raafea; Bashir Kiani, Muhammad Rizwan; Ameer, Muhammad Kamran; Saeed, Arslan Akbar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To investigate the outcomes of energy drink on renal tubules of albino rats. Study Design: Laboratory-based experimental study. Place and Duration of Study: King Edward Medical University, Lahore from Aug 2018 to Dec 2019. Methodology: Group A and B were experimental groups received 1.5ml/kg and 2.2ml/kg body weight of energy drink, respectively. Group C received 1ml/kg body weight of distilled water. Comparison among groups was made by applying One-Way ANOVA for quantitative variables. Tukey’ test was used for post hoc analysis. For qualitative variables, chi-square test was applied to make comparison among groups Results: The mean initial and final weight of animals was around 152.7 ± 5.3g and 171.9 ± 5.1g, respectively. The mean paired kidney weight, relative tissue weight index, length and width of kidneys for all three groups were found insignificant. Microscopic examination showed tubular vacuolization in groups A and B showing p-value of 0.027. Conclusion: Consumption of energy drinks results in histopathological injury of epithelial cells of renal tubules.